Molecular mobility of amorphous N-acetyl-α-methylbenzylamine and Debye relaxation evidenced by dielectric relaxation spectroscopy and molecular dynamics simulations. Issue 2 (13th December 2018) - Atawa, Bienvenu; Correia, Natália T.; Couvrat, Nicolas; Affouard, Frédéric; Coquerel, Gérard; Dargent, Eric; Saiter, Allisson
Abstract : Molecular mobility of NAC-MBA molecule is described by means of DRS, FSC and MD simulations. Abstract : The present work focusses on the molecular mobility characterization of amorphous N -acetyl-α-methylbenzylamine (Nac-MBA) by Broadband Dielectric Relaxation Spectroscopy (DRS) coupled with Fast Scanning Calorimetry (FSC) and Molecular Dynamics (MD) simulations covering over 12 decades in the frequency range. This study reveals another example of a secondary amide that shows a very intense Debye-like contribution (almost 90% of the global dielectric intensity) in addition to the structural α-relaxation and secondary Johari–Goldstein β-relaxation. The D- and α-relaxations are separated by about one decade (in frequency) and their relaxation times follow a near parallel temperature evolution (Vogel–Fulcher–Tammann–Hesse). The micro-structure of Nac-MBA has been investigated from MD simulations. It is shown that the intense Debye-like process emanates from the formation of linear intermolecular H-bonding aggregates (precursors of the crystalline structure) generating super-dipole moments.